Palaeographical observations on four medieval fragments of the Gesta Danorum of Saxo Grammaticus in The Royal Library - Gullick, Michael (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Michael Gullick: Palaeographical observations on four medieval fragments of the Gesta Danorum by Saxo Grammaticus in the Royal Library. The four fragments of a total of three parchment sheets from one or more Saxo manuscripts from the 1300s, found and published between 1855 and 1877, and now archived in Capsule NKS 570 2º, were for a long time considered to belong to the same codex, but Ellen Jørgensen pointed out in 1926 that Fragment III, the Plesner fragment, represented an independent codex. The common origin of Fragments I and II, the Kall Rasmussen fragment and the Lassen fragment, respectively, was further substantiated by Erik Kroman in 1962 and Karsten Friis-Jensen in 1988. This paper demonstrates that, in spite of the fact that all three fragments share many codex-related and palaeographical characteristics, especially punctuation, very likely placing them in a Cistercian environment (there were 10 monasteries of this order in Denmark, including the Sorø Monastery established by Absalom), there are basic but overweighing reasons to assume that the three wholly or partially preserved leaves derive from three different manuscripts of the same size and make-up and that they were produced in the same environment, a possible indication of a specific project in the century after Saxo in the interests of promoting his work. The author points out that detailed palaeographical studies of the considerable number of manuscript fragments in the Royal Library and in the National Archives, many of which may be assumed to derive from manuscripts of Danish origin, could presumably shed more light on book production in Denmark in the 1300s and hence also on the questions discussed in the paper.